Perfil epidemiológico de portadores de pé diabético submetidos à amputação de membro inferior - OLIVEIRA, Ingrid Saraiva de (2019)
A diabetic ulcer is a set of changes in the foot holder of Diabetes Mellitus - pathology defined as multiple etiology syndrome, arising from the absence or inability of insulin to properly exert its effects in the body - resulting from neuropathy,, and others and increased susceptibility to infection due to biomechanical changes, even leading to deformities. Although this complication is extremely common in diabetic patients, usually occurring on average ten years after the onset of the disease and associated infections can progress to non-traumatic lower limb amputations. It is not known precisely its real incidence, a fact that interferes with the quality of the system provided by nurses, either preventive or curative. Given this, the health team is of fundamental importance in the education process and prevention of diabetic patients, especially in preventing complications in the legs, diabetes mellitus (DM) is one. Thus, studies that show indicators of foot ulcers in diabetic patients, thus allowing follow current trends of the disease in order to prevent their occurrence and anticipate the diseases, improving the quality of life of patients and facilitating their recovery It is extremely important. Thus, this study aimed to trace the epidemiological profile of a group of patients undergoing lower limb amputation for diabetic ulcer. To find answers to research questions we opted for descriptive transversal study of quantitative nature, that is, seeking to determine the distribution of disease or health-related conditions, according to the time, place and / or the characteristics of individuals. The search lasted during their months of April and May of 2015, the active search for diabetics who underwent amputation of the lower limbs, totaled the number of 61 patients. These patients mostly were male, the brown race, elderly, alcoholics, had DM type 2. They also showed higher incidence of amputations in the feet and had not undergone previous amputations on results found during search it is expected to stimulate a commitment on the care that diabetes asks and especially care for the feet of a diabetic as this may influence both aesthetically as socioeconomically in the life of a person, and that the higher amputation or higher the numbers amputations, the greater the economic damage this social psychological ill.